2009
DOI: 10.1097/jto.0b013e3181a99ff6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Pulmonary Function Test (PFT) Changes After Stereotactic Body Radiotherapy (SBRT) for Stage I Lung Cancer in Medically Inoperable Patients

Abstract: (1) SBRT was well tolerated and PFT changes were minimal. (2) Central lesions were safely treated with 50 Gy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 31 publications
5
72
1
1
Order By: Relevance
“…In a previous study by Henderson et al [23], baseline FEV 1 significantly predicted for post-treatment survival, and patients with poor pulmonary function had significantly better survival. Another study, from Stephans et al [24], showed similar results. As underlined by Stanic et al [10], these findings might be explained by the higher rate of deaths in patients medically inoperable for reasons other than poor pulmonary function.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In a previous study by Henderson et al [23], baseline FEV 1 significantly predicted for post-treatment survival, and patients with poor pulmonary function had significantly better survival. Another study, from Stephans et al [24], showed similar results. As underlined by Stanic et al [10], these findings might be explained by the higher rate of deaths in patients medically inoperable for reasons other than poor pulmonary function.…”
Section: Discussionmentioning
confidence: 58%
“…This recommendation is based on the results of several prospective phase II trials [2], [3], [4], [5] and [6], as well as large observational studies [7], [8] and [9], with variable follow-up intervals: most of them were limited to spirometric parameters and diffusing capacity for carbon monoxide (Diffusion Lung capacity for Carbon monoxide, D L CO). Recently, a more comprehensive analysis of "complete" Pulmonary Function Tests (including blood gas analysis) was reported, on a series of patients enrolled in the RTOG 0236 phase II trial of SABR in inoperable patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…No proper comparison of SABR and segmentectomy functional consequences can be performed because of the lack of randomised trials. Several studies report PFT measured before and after SABR, but a comparison with surgical series is hazardous because of strong differences in patient characteristics ( patients in SABR studies are older and have more degraded lung function) and study design [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The SABR PFT results suggest that the mean loss of lung function may be lower after SABR than after segmentectomy, but this needs to be confirmed.…”
Section: Future Prospectsmentioning
confidence: 99%
“…[1][2][3] Fatigue, pulmonary toxicity, chest wall toxicity and brachial plexopathy are reported side effects. [2][3][4][5][6][7] Chest wall toxicity includes skin reactions (erythema, ulceration and fibrosis), chest wall pain and rib fracture. 5,[8][9][10] The duration of chest wall pain varies from transient to several weeks or longer and usually occurs more than 6 months after SABR.…”
Section: Introductionmentioning
confidence: 99%